2019
DOI: 10.1021/acsomega.8b02325
|View full text |Cite
|
Sign up to set email alerts
|

Condensate Oil-Tolerant Foams Stabilized by an Anionic–Sulfobetaine Surfactant Mixture

Abstract: Foams are widely used to remove liquid loading at the bottom of gas wells to improve natural gas production. However, it becomes ineffective when a gas well contains a large amount of hydrocarbon condensate because oil will rupture the foams. In this work, condensate oil-tolerant foams were developed and stabilized by a mixture of cocamidopropyl hydroxyl sulfobetaine (CHSB) and sodium dodecyl sulfate (SDS). The foam properties are examined at different temperatures under atmospheric conditions and high pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 45 publications
2
12
0
Order By: Relevance
“…Surface-active agents, commonly known as surfactants, are amphiphilic molecules with widespread use in several industrial processes to achieve the long-lasting stability of nanocolloidal suspensions, emulsions, , and foams. , In fact, when two or more immiscible phases are mixed, the addition of surfactants promotes their adsorption at the phases’ interface thereby lowering the surface free energy and avoiding coalescence and separation of phases. The success of the industrial processes treating surface-active agents relies on a good prediction of the adsorption isotherm curves which connect the concentration of surfactants in suspension with the quantity adsorbed at the interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Surface-active agents, commonly known as surfactants, are amphiphilic molecules with widespread use in several industrial processes to achieve the long-lasting stability of nanocolloidal suspensions, emulsions, , and foams. , In fact, when two or more immiscible phases are mixed, the addition of surfactants promotes their adsorption at the phases’ interface thereby lowering the surface free energy and avoiding coalescence and separation of phases. The success of the industrial processes treating surface-active agents relies on a good prediction of the adsorption isotherm curves which connect the concentration of surfactants in suspension with the quantity adsorbed at the interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…ISGF is made up of a foaming agent, reactants, and a catalyst. According to our previous work, , the CHSB-SDS mixture has superior foaming ability under the Western Sichuan Gasfield, so this surfactant pair was still chosen as the foamer in this work. To develop the ISGF system, different reactants and catalysts were evaluated to find an optimized one.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to the former two forms, liquid foamers are also more easily customized to target specific areas and offer great application versatility whether it be batch or continuous treatment as an artificial lift. While various surfactants including cationic, anionic, and amphoteric ones or their mixture packages were used, ,, the selection of the proper surfactants depends on the type and volume of the produced liquids. , For example, the salinity of the water or hydrocarbon condensates requires special and more tailor-designed agents. Orta and co-workers developed a specifically designed foamer for treating liquid-loaded wells with higher condensate cuts in South Texas, and Qu et al , reported a ternary foamer system composed anionic, zwitterionic, and fluorocarbon surfactants, which can tolerate condensate up to 50% and has been successfully used in 12 condensate-rich natural gas wells. To minimize the corrosion of the pipelines, Campbell and co-workers introduced a corrosion inhibitor into the foamer system to unload liquids from gas wells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This unique property is widely used in the petroleum industry. Cationic, anionic, and non-ionic surfactants can be used to improve oil recovery. , Cationic surfactants are positively charged and are easily adsorbed on the surface of the formation; anionic surfactants have the ability to reduce the interfacial tension between crude oil and water and change the wettability of the reservoir from lipophilic to hydrophilic. However, many studies have shown that anionic surfactants are easily precipitated in brine with relatively high salinity; , non-ionic surfactants have unique advantages in improving salt resistance and wettability, but their ability to reduce interfacial tension is limited and the existence of cloud points restricts their promotion in oil fields. , At present, there are two types of surfactants that are approved for use in high-salt oil reservoirs: anionic–non-ionic surfactants and zwitterionic surfactants.…”
Section: Introductionmentioning
confidence: 99%